FINANCIAL PERFORMANCE ANALYSIS BEFORE AND AFTER COMPANY ACQUISITION: CASE STUDY IN PT. INDOSAT TBK - Daryanto, Wiwiek Mardawiyah; Alfathan, Irfan Rizky; Siregar, Yunandra Reza Nugraha (Advances in Social Sciences Research Journal, 2020)
Telecommunications companies in Indonesia have increased revenue from data services. This is due to the increased penetration of smartphones in Indonesia and the wider coverage of 4G LTE services. Indosat Ooredoo, company name is PT Indosat Tbk. with the previous name Indosat is one of the companies in Indonesia who provides telecommunications services and networks. In 2013, the Qatar telecommunications company controlled 65% of Indosat's shares and planned to replace all of its owned companies with the name Ooredoo Asia Pte. Ltd. On November 19, 2015 Indosat finally changed its identity and logo with the name Indosat Ooredoo. Because of that, the intent of this case is to know the financial performance of Indosat Ooredoo and to verify the significant differences between financial performances before and after the acquisition in 2015. Data collected from Indosat Ooredoo financial statements are taken with two periods: before the acquisition (2012-2015) and after the acquisition (2016-2019). Paired sample t-test and financial ratio analysis method were used to analyze the entire data. The research proves that Indosat Ooredoo is in a very good financial condition with good performance after the acquisition. Even if several factors are not significantly improved. The author believes that the research will be useful to prove the true effect of acquisition decisions within Indosat Ooredoo Company.